Preventing Financial Statement Fraud in State-Owned Entreprises: The Strategic Role of the Audit Committee in Moderating Financial Pressure and Corporate Governance - Pratiwi, Ajeng; Nugroho, Lucky (School of Accountancy, University of Agung Podomoro, 2024)
The financial statement fraud case in Indonesian State-Owned Enterprises (SOEs) raises concerns related to transparency and accountability of corporate governance. This phenomenon indicates a gap between strict regulations and weak supervision implementation. Previous studies have shown inconsistent results related to factors affecting financial statement fraud, so further studies are needed. This study analyzes the influence of return on assets (ROA), independent commissioners, and company size on financial statement fraud, and it evaluates the audit committee's role as a moderation variable. Using panel data regression and Moderated Regression Analysis (MRA), this study processed data from 29 state-owned companies listed on the IDX for 2018–2023. The study results showed that ROA and Company Size positively affected financial statement fraud, while Independent Commissioners had a negative effect. The Audit Committee has been proven to weaken the negative impact of ROA and Company Size and strengthen the influence of Independent Commissioners in reducing fraud. This study expands the application of Agency Theory in the context of SOEs. It emphasizes the importance of strengthening supervision through the Audit Committee and Independent Commissioners to prevent the manipulation of financial statements.